Ozone Regional Non-Invasive (ORNi) Therapy in Combination with Nursing Management of Diabetic Foot Ulcer Care: A Case Study - Arisanty, irma Puspita; Dahlia, Debie (Jurnal Keperawatan Soedirman, 2021)
Background: DFU patients must be treated properly less than 30 days to prevent infection spread to the bone, causes smaller opportunity to recovery and higher risk for amputation. Ozone therpay has a clearer clinical effect, affects the wound healing process, it can be seen by decreasing the length of stay. Method: Case studies of 3 DFU patients who were given ORNi therapy. Wound evaluation using Bettes-Jenssen Assessment tool skoring system. Results: There were significant improvement in these cases after given a noninvasive regional ozone therapy (ORNi) as a combination in standard treatment for 5 – 7 times. There are no sign of infection, granulation and epithelization processes were running optimal and exudate production was controlled. Conclusions and recommendation: Using ORNi therapy as an adjunct to standard care has shown a significant improvement. The rate of granulation and epithelization during 15 days of treatment has an average growth rate of granulation and epithelization up to 22%. Researchers recommend to do more research with suficcient sample size related to the use of ozone therapy as an adjunct in wound care.